2016
DOI: 10.1097/md.0000000000003473
|View full text |Cite
|
Sign up to set email alerts
|

Should Splenic Hilar Lymph Nodes be Dissected for Siewert Type II and III Esophagogastric Junction Carcinoma Based on Tumor Diameter?

Abstract: The aim of the study is to identify the value of a spleen-preserving No. 10 lymphadenectomy (SPL) for Siewert type II/III adenocarcinoma of the esophagogastric junction (AEG).From January 2007 to June 2014, 694 patients undergoing radical total gastrectomy for Siewert type II/III AEG were analyzed. Oncologic outcomes were compared between SPL and no SPL (No. 10D+ and No. 10D–) groups.The incidence of No. 10 lymph node metastasis (LNM) was 12.3%. No significant differences in the incidence of No. 10 LNM were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…This suggests that No. 10 lymphadenectomy is recommended for Siewert type III AEG with a tumor diameter >4 cm (26). Although Siewert type III cancers had more metastatic lymph nodes in this study, the metastasis rate of PLNs was comparable between Siewert type II and Siewert type III AEGs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This suggests that No. 10 lymphadenectomy is recommended for Siewert type III AEG with a tumor diameter >4 cm (26). Although Siewert type III cancers had more metastatic lymph nodes in this study, the metastasis rate of PLNs was comparable between Siewert type II and Siewert type III AEGs.…”
Section: Discussionmentioning
confidence: 53%
“…However, these reports do not present a detailed investigation of the IEBLDs based on tumor diameter. For all we Siewert type III AEG with a tumor diameter >4 cm (26). This suggests that No.…”
Section: Discussionmentioning
confidence: 82%
“…[ 22 ] In addition, evidence suggests that spleen-preserving No.10 lymphadenectomy (SPL) may improve the prognosis of Siewert type III adenocarcinoma (tumor diameter ≥4 cm) of the EGJ, while for patients with Siewert type II or III adenocarcinoma (tumor diameter <4 cm), SPL may be omitted without reducing the survival rate. [ 23 ] Although the above-mentioned surgical approaches have some limitations, they provide new methods for the treatment of EGJ cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results may be explained by the fact that survival time was mainly determined by the UICCs [ 5 ]. On the other hand, a previous study has demonstrated that Siewert-type III AEG with tumor diameters >4 cm has a high relative frequency of splenic hilar metastasis [ 19 ]. Therefore, AEG often combined splenic hilar resection in this study.…”
Section: Discussionmentioning
confidence: 99%